2003
DOI: 10.1046/j.1365-2826.2003.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Produced by a Novel Nitric Oxide Synthase Isoform is Necessary for Gonadotropin‐Releasing Hormone‐Induced Growth Hormone Secretion Via a cGMP‐Dependent Mechanism

Abstract: The involvement of nitric oxide (NO) in the regulation of goldfish growth hormone (GH) secretion was further characterized using primary cultures of dispersed goldfish pituitary cells. Western blots revealed the presence of an inducible nitric oxide synthase (iNOS)-like protein of approximately 120 kDa in cytosol/plasma membrane extracts. By contrast, brain NOS-immunoreactive proteins of approximately 120-140 kDa were occasionally detected in a cytoskeleton/organelle fraction but were absent from cytosol/plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 54 publications
(73 reference statements)
0
40
0
1
Order By: Relevance
“…In goldfish, NOS immunoreactivity is present in pituitary somatotropes and the NOS/NO signal transduction cascade mediates gonadotropin releasing hormone-stimulated GH release [29,30]. With respect to PACAP, Ohnishi T and co-workers (2008) demonstrated that this peptide stimulated neuronal nitric oxide synthase translocation, mediated by protein kinase C and protein kinase A via the PAC1-receptor [31].…”
Section: Discussionmentioning
confidence: 99%
“…In goldfish, NOS immunoreactivity is present in pituitary somatotropes and the NOS/NO signal transduction cascade mediates gonadotropin releasing hormone-stimulated GH release [29,30]. With respect to PACAP, Ohnishi T and co-workers (2008) demonstrated that this peptide stimulated neuronal nitric oxide synthase translocation, mediated by protein kinase C and protein kinase A via the PAC1-receptor [31].…”
Section: Discussionmentioning
confidence: 99%
“…While NADPHd positive cells were encountered in the pituitary of swordtail (Anken and Rahmann, 1996) and 10 species of catfish (Jadhao et al, 1999), NOS expression was detected in the pituitary of O. niloticus (Bordieri et al, 2003) and in the somatotropes of goldfish pituitary (Uretsky and Chang, 2000). While NO was found to be necessary for the GnRH induced GH secretion (Uretsky et al, 2003), dopamine stimulated GH release was mediated by NO in goldfish (Mitchell et al, 2008). Several immunoreactive cells and fibers were seen in the rostral pars distalis, proximal pars distalis and pars intermedia of the pituitary gland of C. batrachus.…”
Section: Hypothalamo-hypophysial Neurons and Pathwaysmentioning
confidence: 99%
“…The hypothalamo-hypophysial system of a range of teleosts was reported to be rich in NADPHd/ NOS expression (Jadhao et al, 1999;Bordieri et al, 2003). While nNOS containing cells have been reported in the pituitary of S. multipunctatus (Jadhao and Malz, 2003), NO is necessary for the GnRH induced GH secretion in goldfish (Uretsky et al, 2003).…”
mentioning
confidence: 99%
“…In another paradigm, SRIF inhibited the NO-mediated stimulation of GH release in goldfish pituitary somatotrophs (Yunker et al, 2003).…”
Section: Gh Regulationmentioning
confidence: 99%
“…Somatostatin was found to exert a dual role in previous studies had supported a functional role of NO in GH release (Pinilla et al, 1999, Bocca et al, 2000. NO generated cGMP was shown to be a necessary signal transduction component of GnRH-induced GH secretion (Uretsky et al, 2003). Luque et al (2005) reported that NOS/NO plays a critical role in the stimulatory actions of low concentrations of SRIF on pig GH release, but without the involvement of cGMP.…”
Section: Gh Regulationmentioning
confidence: 99%